2001
DOI: 10.1007/s002560100355
|View full text |Cite
|
Sign up to set email alerts
|

Malignancy in chronic ulcers and scars of the leg (Marjolin's ulcer): a study of 21 patients

Abstract: Chronic ulcer present for decades that then undergoes malignant change is a disease of developing countries where patients only consult physicians when they have developed complications such as pain, bleeding or tissue necrosis. Chronic ulcers may require to be biopsied at regular intervals as malignant change in these ulcers is directly related to their duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
85
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(90 citation statements)
references
References 18 publications
2
85
0
2
Order By: Relevance
“…With improvements in antibiotic and surgical therapy of chronic osteomyelitis and chronic ulcers, the incidence of these cancers in industrialized countries has decreased substantially. Today, most cases are reported in areas with poor access to health care, where tropical ulcers, leprosy, and inadequate burn and wound care are more common (127,226). The tumors in Marjolin ulcers are generally very aggressive, and metastases are found at diagnosis in 14% to 40% of cases.…”
Section: Alterations Of Normal Host Responses Chronic Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…With improvements in antibiotic and surgical therapy of chronic osteomyelitis and chronic ulcers, the incidence of these cancers in industrialized countries has decreased substantially. Today, most cases are reported in areas with poor access to health care, where tropical ulcers, leprosy, and inadequate burn and wound care are more common (127,226). The tumors in Marjolin ulcers are generally very aggressive, and metastases are found at diagnosis in 14% to 40% of cases.…”
Section: Alterations Of Normal Host Responses Chronic Inflammationmentioning
confidence: 99%
“…Almost exclusively, the histopathology of the carcinoma is of the squamous cell type (161), either spinocellular or verrucous (20,252). However, basal cell carcinoma has also been reported (226).…”
Section: Alterations Of Normal Host Responses Chronic Inflammationmentioning
confidence: 99%
“…4 Tenopyr and Silverman reported that the time of progression of an ulcer has to be at least three years for malignant transformation to be considered; otherwise, the hypothesis of a primary lesion causing the ulcer should be raised. 5 Malignant transformation of a chronic sore is a dynamic process that remains to be fully clarified; however, various factors such as repeated trauma, immunodeficiency, growth factors present in the exudate and changes in tissue vascularization and genetic predisposition may contribute. The onset and/or intensification of pain, 1 fetid suppuration of abnormal volume, 1 exophytic and friable areas, an increase in the size of the lesion, hardening and a tendency to hemorrhage 1 are signs that are strongly indicative of malignant transformation.…”
Section: Discussionmentioning
confidence: 99%
“…С тех пор рак, развившийся в рубцах, носит название язвы Маржо-лена [2][3][4]. Впоследствии это определение было су-щественно расширено, и в настоящее время многие специалисты под язвой Маржолена понимают пло-скоклеточный рак, возникающий в хронических ра-нах и язвах любой этиологии [5,6]. Истинная часто-та такого опухолевого перерождения неизвестна, поскольку в литературе обычно описываются лишь отдельные больные.…”
unclassified